2007
DOI: 10.4028/www.scientific.net/msf.537-538.137
|View full text |Cite
|
Sign up to set email alerts
|

MAgPP an Effective Coupling Agent in Rice Husk Flour Filled Polypropylene Composites

Abstract: Different properties (tensile strength, elongation, modulus, impact strength) of rice husk (RH) reinforced polypropylene (PP) coupled by Maleic-Anhydride grafted Polypropylene (MAgPP) have been investigated. MAgPP is an effective coupling agent, not only in cellulosic-fibre filled polyolefine composites, but in rice husk flour filled polypropylene composite systems as well. It gives a utilizable construction polymer matrix composite (PMC) material even at a 40 wt.% RH filling degree. The strength and modulus i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…However, a negative correlation between fiber content and NI strength has also been reported in other many NFTC studies (Li et al, 2001(Li et al, , 2012Marcovich and Villar, 2003;Yang et al, 2006;Czél and Kanyok, 2007;Ashori et al, 2008;He et al, 2008;Nourbakhsh and Ashori, 2008;Yao et al, 2008;Liu et al, 2009;Guo et al, 2010). The reasons proposed for this included: 1) a change in the nature of the fracture from ductile to brittle reduction of the deformability of the polymer (Mohanty and Nayak, 2010).…”
Section: Discussion Of Fiber Content Effectsmentioning
confidence: 65%
See 1 more Smart Citation
“…However, a negative correlation between fiber content and NI strength has also been reported in other many NFTC studies (Li et al, 2001(Li et al, , 2012Marcovich and Villar, 2003;Yang et al, 2006;Czél and Kanyok, 2007;Ashori et al, 2008;He et al, 2008;Nourbakhsh and Ashori, 2008;Yao et al, 2008;Liu et al, 2009;Guo et al, 2010). The reasons proposed for this included: 1) a change in the nature of the fracture from ductile to brittle reduction of the deformability of the polymer (Mohanty and Nayak, 2010).…”
Section: Discussion Of Fiber Content Effectsmentioning
confidence: 65%
“…The initial addition of filler led to a significant drop in the impact properties, particularly in the case of NI and UI strength of wood flour composites and UI strength of rice husk flour composites. Czél and Kanyok (2007) studied the effect of fiber content (0-50 wt%) on injection molded rice husk flour reinforced PP with MAPP as coupling agent. Results showed that the Izod NI strength decreased with increasing reinforcement content.…”
Section: Fiber Content Effectsmentioning
confidence: 99%
“…In the case of the 6 wt% MAPP composite, the regression curve seem to stabilize, but in the case of the 8 wt%, MAPP content the curve shows a tendency to descent. A strong interface can reduce the deformability of the material and increase its fragility, this phenomenon increases with increasing percentages of reinforcement [ 36 ]. Some authors announce that high percentages of coupling agents can promote self-entanglement between the compatibilizer and cause a descent of the impact strength [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Maleic anhydride polyethylene (MAPE) on RH/PE composites significantly improves the mechanical and physical properties, with the best properties at 6 wt% (Yang et al 2005, Chen et al 2015, Ab Ghani et al 2014, Ghofrani 2011, Tong et al 2014. Using maleic anhydride polypropylene as a binding agent improves tensile mechanical and physical properties of the composite, with the best properties at 5 wt% (Yang et al 2005, Kim et al 2007, Aminullah et al 2010, Rosa et al 2009b, Czél and Kanyok 2007. Scanning electron microscopy (SEM) micrographs indicate that using a binding agent improves interfacial adhesion in the composite (Yang et al 2005, Aminullah et al 2010, Rosa et al 2009b, Ab Ghani et al 2014, Ghofrani 2011.…”
Section: Introductionmentioning
confidence: 99%